The day Fin flooded the world - Stower, Adam (Andersen Press, 2021)
Fin is extremely forgetful he wears slippers to school and comes home without his trousers. So it's no surprise when he leaves the tap running until it floods the world! Who will be outraged, and who will be overjoyed?
Keywords: Überschwemmung; Vergesslichkeit; Junge; Boys / Juvenile fiction; Memory / Juvenile fiction; Floods / Juvenile fiction; Animals / Juvenile fiction; Garçons / Romans, nouvelles, etc. pour la jeunesse; Inondations / Romans, nouvelles, etc. pour la jeunesse; Animals; Bilderbuch